Current status of localized submental fat treatment with sodium deoxicolate (ATX-101) - Cristina Ibáñez-Vicente; Miguel Carrato-Gomez; Luigi Meccariello; Umberto Ripani; Michele Bisaccia (Medicinski glasnik, 2020)
Aim: Facial aesthetics is at present a concept intricately linked to the degree of self-esteem. Unwanted submental fat (SMF) leads to an unattractive submental profile. Sodium deoxicolate (ATX) -101 is the only injectable drug approved to decrease submental fat of moderate to severe intensity. Methods: We carried out a bibliographic review in PubMed using the key words: deoxycholic acid, ATX-101, and submental fat. Only complete articles published between 2009 and 2019, and focused on submental fat were reviewed, excluding those articles relating to that spoke of deoxycholate in the treatment of fat in other locations or in which deoxycholate was associated with other drugs. Results: In several phase III clinical trials, injection of 2 mg/cm2 deoxycholic acid in SMF has reduced moderate-severe fullness compared to the placebo group. These results were maintained in most cases during a long follow-up period. Injections of deoxycholic acid are generally well tolerated, with limited adverse effects in the treatment area, with a mild and complete resolution without sequelae. However, not all patients with SMF are suitable for deoxycholic acid therapy, and therefore a proper selection is very important to achieve the desired aesthetic results. Conclusion: Deoxycholic acid injections are effective and are a generally well-tolerated, minimally invasive option for the treatment of moderate to severe intensity SMF in selected adults.
Keywords: adipocitolysis; double chin; lipolysis